2020
DOI: 10.1093/mnras/staa388
|View full text |Cite
|
Sign up to set email alerts
|

Are long-term N-body simulations reliable?

Abstract: N-body integrations are used to model a wide range of astrophysical dynamics, but they suffer from errors which make their orbits diverge exponentially in time from the correct orbits. Over long time-scales, their reliability needs to be established. We address this reliability by running a three-body planetary system over about 200 e-folding times. Using nearby initial conditions, we can construct statistics of the long-term phase-space structure and compare to rough estimates of resonant widths of the system… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
3
13
0
Order By: Relevance
“…Thus, although an initial small difference can grow exponentially so that individual N -body models cannot reproduce the exactly same evolution of a real cluster, the statistical means are meaningful. A similar result in the orbits of planets is found in Hernandez et al (2020).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Thus, although an initial small difference can grow exponentially so that individual N -body models cannot reproduce the exactly same evolution of a real cluster, the statistical means are meaningful. A similar result in the orbits of planets is found in Hernandez et al (2020).…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, Nesc of individual models is not reliable; to understand the properties of escapers in a low-mass star cluster, it is necessary to obtain ensemble statistics. Hernandez et al (2020) found a similar behaviour for the phase space structure of planetary dynamics.…”
Section: Number Of Escaperssupporting
confidence: 60%
See 2 more Smart Citations
“…So without fusion the angular momenta L I (t) and L G (t) with Newton's discrete dynamics are conserved separately, and at a fusion the total angular momentum is still conserved but with an exchange of angular momentum with δL I (t) = −δL G (t). The exact classical discrete dynamics with fusion of colliding objects can be used to explore the self-assembly at the emergence of planetary systems and to investigate the stability and chaotic behaviour of solar systems [26].…”
Section: The Discrete Algorithm For Fusion Of Classical Objectsmentioning
confidence: 99%